A Great Event - Increase Engagement - Kaļva, Artūrs; Ribalkina, Elizabete; Narbute, Katrīna; Šmits, Dins (ICAReAlumni Conference Proceedings, 2019)
Introduction and aim: Activities of alumni organisation in Latvia and The Baltic States are a new phenomenon. It allows us to look for the best approach and solutions to attract university graduates. The goal of this research was to find the best tools for engaging university graduates of specific scientific group in alumni organisation. The hypothesis of this research was that a specific event for a certain group of alumni can enhance the recognition of Alumni organisation and their willingness to engage in alumni action. Research methodology: To prove this hypothesis an event for a certain group of alumni was organised, it included three parts: success stories of alumni, reunion and networking activities. The research is based on the analysis of the growth dynamics of the number of graduates and analysis of the feedback gained through interviews of specific scientific group before and after activities. Results: In result, 167 guests who belong to a certain group had attended the event. Before the event 7% of all alumni association members were representatives of certain group, but after the event, there were 26% of group representatives among alumni association members. This means that 46% of the guests of the event became members of the association, which increased the total number of members of the association to 19%. Conclusion: A certain group of alumni was enhanced after the event with specific activities. This proved that specific events can increase the recognition of alumni organisation and the willingness to engage in alumni action. This provides the basis for future research about segmentation of alumni and allows to explore the types of engagement of each group.